THE INFLUENCE OF PRICE, PROMOTION, AND SERVICE QUALITY ON THE DECISION TO STAY AT KARTIKA CHANDRA HOTEL JAKARTA - Ade Yusuf; Hasanudin Hasanudin (International Journal Multidisciplinary Science, 2024)
This study examines the influence of price, promotion, and service quality on the decision to stay at the Kartika Chandra Hotel in Jakarta. In a competitive hospitality industry, pricing strategy, effective promotions, and superior service quality are critical in influencing consumer choice. Utilizing a quantitative approach with data collected from 100 respondents, the research analyzes the impact of these variables on guests' decision-making processes. Results reveal that price, promotion, and service quality each have a significant positive influence on the decision to stay, with combined factors accounting for 47% of decision variance. These findings suggest that hotels can increase guest retention by enhancing these three elements, focusing on flexible pricing, impactful promotions, and consistent service quality. The study offers insights for hotel management to improve customer satisfaction and maintain a competitive edge in the hospitality sector.